2019
DOI: 10.3390/antiox8120574
|View full text |Cite
|
Sign up to set email alerts
|

Batryticatus Bombyx Protects Dopaminergic Neurons against MPTP-Induced Neurotoxicity by Inhibiting Oxidative Damage

Abstract: Oxidative stress plays an important role in the degeneration of dopaminergic neurons in Parkinson’s disease (PD). Altered redox homeostasis in neurons interferes with several biological processes, ultimately leading to neuronal death. Oxidative damage has been identified as one of the principal mechanisms underlying the progression of PD. Several studies highlight the key role of superoxide radicals in inducing neuronal toxicity. Batryticatus Bombyx (BB), the dried larva of Bombyx mori L. infected by Beauveria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Western blotting was performed according to previously published methods 16‐18 . The cells and tissues were lysed with protein extraction buffer to obtain whole‐protein extracts.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed according to previously published methods 16‐18 . The cells and tissues were lysed with protein extraction buffer to obtain whole‐protein extracts.…”
Section: Methodsmentioning
confidence: 99%
“…As we all know, the pathogenesis of PD is mediated by excessive production of ROS, which will eventually lead to the loss of mitochondrial membrane potential, resulting in the activation of caspase cascade [38][39][40][41]. In this study, PQ induced oxidative stress in SH-SY5Y cells, and the production of ROS was the initial event that mediated the death of SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 64%
“…2). Previous reports showed that dairy administration of ropinirole has neuroprotective effects at 1.0 or 2.0 mg/kg/d 12,18) in mice. When ropinirole (2.0 mg/kg/d) was continuously administered by an osmotic pump, the blood concentration was measured at 2.93-8.96 ng/mL (Table 1).…”
Section: Discussionmentioning
confidence: 95%